Immersive technology-driven investigations on influence factors of cognitive load incurred in construction site hazard recognition, analysis and decision making. (April 2021) - Han, Yu; Diao, Yongsheng; Yin, Zhenzhen; Jin, Ruoyu; Kangwa, Joseph; Ebohon, Obas John
Highlights: The study adopted immersive virtual reality to gauge safety performance. The immersive experiments covered hazard recognition, analysis, and reaction. Task mode and time pressure were adopted as two independent variables. Double tasking mode increased individuals' cognitive load. Time pressure is a double-edged sward for task performance. Abstract: Digital technologies such as Virtual Reality (VR) are gaining momentum in its use to implement and deepen construction health and safety education. In this study, researchers first developed a VR-driven immersive system incorporating real construction site hazard scenarios. Immersive experiments were then conducted by recruiting 40 individuals in construction-related disciplines. Experimental data were collected to evaluate the effects of tasking mode and time pressure on individuals' cognitive load in performing virtual site tasks. The self-evaluation method and task performance-based data were adopted as the complementary ways to measure individuals' cognitive load in completing given tasks. Compared to the single tasking mode of solely focusing on site hazard recognition, analysis, and reaction, the added secondary task was found significantly increasing individuals' cognitive load and lowering task performance. Time pressure could be a double-edged effect depending on the task feature. Recommendations were provided for real site safety management in balancing employees' wellbeing and site productivity. The current study extends prior research on enhancing construction health and safety where the main focus has been on hazard detection but now incorporates also hazard analysis and reaction. It also leads to more future research such as measuring individuals' cognitive load in a real site environment.